Educação em saúde: sequência didática investigativa sobre leishmaniose no ensino médio - Ana Paula Matos Diniz (2022)
Leishmaniasis is a parasitic disease caused by protozoa of the genus Leishmania and transmitted to humans by the bite of mosquitoes of the sand fly family. Health-related issues can be discussed in the school environment in an investigative way, in order to encourage students to understand how daily habits can influence the emergence or spread of diseases in their community. In recent years, visceral leishmaniasis has expanded to urban areas in Brazil. In Minas Gerais, the municipality of Betim, Belo Horizonte metropolitan area, recorded an increase in the number of new cases from 2015 to 2020. This study aimed to use Leishmaniasis as the subject of an investigative didactic sequence. The activity was developed using an active methodology. Students were invited to research on the topic, prepare concept maps, collect and analyze the data obtained by them. The results allow us to conclude that the investigative activity stimulates students' protagonism and provides significant learning. The products of this didactic sequence were concept maps, questionnaires for data collection, interviews and student presentations.